Source of inoculum and development of bean web blight in Costa Rica - Galindo, J.J.; Abawi, G.S.; Thurston, HD; Galvez, G (Scientific Societies, 1983)
Epidemiology of bean (Phaseolus vulgaris) web blight (BWB) caused by Thanatephorus cucumeris (teleomorph of Rhizoctonia solani) was studied in a field with a history of severe incidence of the disease. Sclerotia and mycelium of T. cucumeris, either free in soil or in the form of colonized debris, were found to be the main sources of inoculum. Inoculation of bean plants occurs mainly by splashing of raindrops containing T. cucumeris-infested soil caused typical BWB symptoms when sprayed onto greenhouse-grown plants. Greenhouse-grown plants incubated in the experimental field on elevated platforms where rain-splashed soil could not reach the plants did not develop BWB symptoms, whereas plants in the same field showed 100% infection. Initial BWB symptoms were observed on the primary leaves 14 days after planting. Trifoliolate leaves were similarly infected by rain-splashed inoculum but more often by advancing hyphae from infected tissues that were also observed causing infection of adjacent plants. A large number of small sclerotia (0.5 1 mm diam.) were produced within 3 days of contact with plants on intact and detached infected tissues. Hymenial layers of T. cucumeris were first observed on the lower stem tissues of 2% of the plants about 28 days after planting. Lesions on leaves that are typical of basidiospore infection remained restricted (2 5 mm) and were observed only in plantings made during the second growing season (September to December). Progress of BWB was very rapid because of the high inoculum level and conducive weather conditions. The infection rate varied between 0.42 0.78 and 0.51 0.94 per unit per week for the cultivars Porrillo 70 (BWB-tolerant) and Mexico 27 (BWB-susceptible), respectively. Regression analysis of the data on BWB development better fitted the compound interest disease model sensu Vanderplank.